Provvidenza e senso: appunti di un viaggio filosofico-teologico all’interno della «storia» (I) - Nitrola, Antonio (Alpha omega, 2001)
Who am I? Where do I come fom and where am I going? Why does evil exist? After this life what is there? These are the basic questions that accompany human existence. Our days are characterized by an increasing mistrust with regard to the human being's cognitive resources. lt is necessary then to delve deeper into man and to be in constant search far truth and meaning. This is an invitation far theologians to pay special attention to the philosophical implications of the word of God in history and its meaning. Therefore it is a question of beginning a joumey on the paths of history, a trip which is not exclusively theological, to be patiently undertaken, to be asked, to be questioned, as perhaps theology is no longer accustomed to do.